Feasibility of Digital Flipbooks as Physics Teaching Media in Terms of Reproduction - Afikah, Adilah; Jumadi, Jumadi; Rohaeti, Eli (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
Various media that utilize technology in implementing teaching materials make the teaching-learning process more innovative and increase students' curiosity. This study aims to develop a digital flipbook for studying physics in reproduction and to validate the developed flipbook. This study applied the research and development (R&D) design using the 4-D model which consists of define, design, develop, and disseminates. This study is only up to the validation stage and revision of the validation results. The validation subjects in this study are 16 people. The result shows that the developed media is valid, totalling 97.51%. It is expected that the digital flipbook of physics in reproduction can be further developed in further research, namely in the implementation stage, to test how effective it is in the science learning process.